Encyclopedia of Aerospace Engineering 2010
DOI: 10.1002/9780470686652.eae156
|View full text |Cite
|
Sign up to set email alerts
|

Turbomachinery Aeroelasticity

Abstract: This paper focuses on the validity of the used assumptions in the development of the Decoupled approaches which predict the aeroelasticity behavior of turbomachinery blades. A Decoupled approach is employed to evaluate the aerodynamic damping and the forced response of a low pressure compressor BluM T M induced by low engine order excitations. The validity of the assumptions like superposition principle, linearity of aerodynamic damping forces and the blade-motion independency of the aerodynamic forces are ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…3 Furthermore, the structural dynamics and unsteady aerodynamic loading caused by bird damage induce a complex aeroelastic response problem that can lead to aeroelastic instability. 4,5 Predicting the aeroelastic behavior of a bird damaged fan blade represents a significant design barrier in the development of improved-efficiency turbofan engines.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…3 Furthermore, the structural dynamics and unsteady aerodynamic loading caused by bird damage induce a complex aeroelastic response problem that can lead to aeroelastic instability. 4,5 Predicting the aeroelastic behavior of a bird damaged fan blade represents a significant design barrier in the development of improved-efficiency turbofan engines.…”
Section: Nomenclaturementioning
confidence: 99%
“…(5). Within ANSYS CFX, the aerodynamic forces are first calculated at each CFD node on the blade surface using Eq.…”
Section: Aerodynamic Load and Structural Deformation Transfermentioning
confidence: 99%
“…The compressor design has an increasing trend towards higher blade loading and thinner blade shape. However, this also increases the occurrence probability of aeroelastic instability which can be mainly divided into forced response, nonsynchronous vibration, acoustic resonance and flutter [1,2]. The former three types rely on the unsteady aerodynamic forces generated by external disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown that any loss of symmetry in the flow field may cause an LEO forced response [ 1 , 4 , 5 , 6 ]. However, the stator vanes of the turbine, as high-temperature components downstream of the combustion chamber, experience creep, fatigue, oxidation and corrosion, and sudden damage failures at the trailing edges occur regularly [ 7 , 8 , 9 ]. Geometric changes in the stator vanes not only affect the work of the stator row but may also destroy the circumferential symmetry of the design flow and cause the LEO forced response on rotor blades.…”
Section: Introductionmentioning
confidence: 99%